The Use of Interactive PowerPoints to Increase Elementary School Student’s Learning Outcomes and Motivation in Mathematics during the Pandemic - Elizabeth Jerika; Disa Evawani Lestari (Mathematics Education Study Program, 2022)
The Covid-19 pandemic has been disturbing every human activity, including education. Schools are shifted to online learning, forcing teachers and students to teach and study from their homes. Several issues that arise due to this are problems with motivations and learning outcomes. In order to increase elementary school students’ learning outcomes and motivation in Mathematics, this research uses an interactive PowerPoint as the learning media. The subjects in this study are 25 students on the grade 6th of a private elementary school in Bekasi, Indonesia. The research methodology is mixed method, the quantitative data was taken by pretest and posttest and the qualitative data by survey questionnaire and interview with the students and mathematics teacher which is also the homeroom teacher. The data was analyzed using paired samples T-Test and thematic analysis. The quantitative results show that the interactive PowerPoint media is able to improve the students' learning outcomes. However, the results had shown an insignificant value of 0.377 and considered as not significant. At the same time, there are unexpected findings from the external factors that cause the result not to be significant, in which the student’s parents and family are involved during online learning. Despite the low significance results, through the interview, both of teachers and students stated that the interactive PowerPoint learning media that was used in mathematics during this pandemic has successfully engaged the students and increased their learning motivations.